Retrospective Study of Feline Panleukopenia Risk Factors in Pet Cats in Madiun - Baroroh, Diana Nova; Tyasningsih, Wiwiek; Praja, Ratih Novita; Rahmahani, Jola; Yunita, Maya Nurwartanti (Jurnal Medik Veteriner, 2023)
This study analyzed the association between risk factors and Feline panleukopenia at the Ichiyo Veterinary Clinic, Madiun using a retrospective method. A total of 2037 data used was secondary data obtained from cat medical and ambulatory reports from January 2018-March 2021. The risk factors analyzed included age, gender, vaccination status, comorbid diseases, housing system, number of cats, and season. Data was presented descriptively and analyzed using Chi-Square analysis. The results showed that the risk factors for Feline panleukopenia were cats aged â‰¤6 months, cats that were not vaccinated, and cats with comorbid diseases. It can be concluded that prevention of Feline panleukopenia can focus on age, vaccination and treatment of potential comorbid diseases in cats.